A lateral flow immunoassay-based survey reveals a low-frequency truncated Solenopsis invicta venom 2-like protein and unique Solenopsis invicta venom 2 protein genotypes in Solenopsis invicta - Valles, Steven M.; Vander Meer, Robert K.; Estep, Alden S. (Frontiers in Insect Science, 2025)
The purpose of this research was to examine the Solenopsis invicta venom 2 protein and transcript among Solenopsis invicta fire ants exhibiting an unusual response to antibody interrogation of this protein. Sequence and phylogenetic analyses combined with Western blotting and lateral flow immunoassay were employed to examine the venom proteins from these fire ants. Genotypic variation was discovered in the Solenopsis invicta venom 2 gene. Many of these unique genotypes exhibited strong identity to the Solenopsis richteri venom 2 ortholog from the congener, Solenopsis richteri. Phylogenetic analysis of these sequences revealed a significant evolutionary relationship with Solenopsis richteri despite being obtained from Solenopsis invicta. A unique, truncated, Solenopsis invicta venom 2-like protein was also discovered in these colonies originating from a unique locus on chromosome 10 where multiple duplication events have apparently copied this gene. These results suggest the possible presence of a cryptic species.